Assessment of patients’ knowledge and perceptions of MRI scans and safety in Saudi Arabia - Alghamdi, Sami A. (Frontiers in Public Health, 2024)
Background: This study was conducted to assess the levels of knowledge about MRI scans and safety measures among patients in Saudi Arabia.This cross-sectional study was conducted at nine Saudi Arabian hospitals and utilized a questionnaire comprising 22 items that evaluated patients' knowledge regarding MRI scans and safety measures, divided into four sections. The questions encompassed patients' sociodemographic data (A), knowledge about MRI (B), safety measures (C), and communication (D). Descriptive statistics were used to characterize the participant demographics and responses.Results: Out of 446 MRI patients, 60.5% correctly identified that MRI does not involve ionizing radiation, and 78% recognized MRI as a diagnostic tool. Further, 94.2% knew that metal objects are not allowed in MRI rooms. However, 80.3% incorrectly believed that pregnant patients cannot undergo MRI at any time, 57% thought the MRI scanner is turned off when not in use, and 72.6% did not recognize any MRI-compatible devices. About 62% were unaware of the need for kidney function tests with contrast agents, and 43% reported anxiety during MRI scans. Overall, 57% of the patients had limited knowledge of MRI safety, with 39.5% considering their understanding adequate. Educational attainment and employment status were significantly associated with improved MRI knowledge. Most participants sought information from healthcare professionals.This study highlights the need to educate patients about MRI procedures and safety protocols. Significant gaps remain in patients' knowledge, especially regarding safety measures.Higher levels of educational attainment and employment status were linked to greater levels of MRI knowledge, suggesting the importance of targeted educational interventions. Healthcare professionals were the patients' main information sources; nevertheless, comprehensive and accessible information is necessary. Improved communication and training for healthcare providers can enhance patient understanding and experiences during MRI scans.